The relationship between tacrolimus concentration-dose ratio and genetic polymorphism in patients subjected to renal transplantation - Rančić Nemanja; Vavić Neven; Cikota-Aleksić Bojana; Magić Zvonko; Mikov Momir; Bokonjić Dubravko; Šegrt Zoran; Dragojević-Simić Viktorija (Vojnosanitetski Pregled)
Background/Aim. Tacrolimus concentration-dose ratio as a potential therapeutic drug monitoring strategy was suggested to be used for the patients subjected to renal transplantation. The aim of this study was examining the relationship between tacrolimus concentration-dose ratio, suggested to be used as a therapeutic drug monitoring strategy and the polymorphisms of genes encoding the most important enzymes, such as CYP3A5 and CYP3A4, as well as the transporter P-glycoprotein, for its metabolism and elimination. Methods. The study was designed as a prospective case series study, in which the unit of monitoring was the outpatient examination of 54 patients subjected to renal transplantation. Genotyping was performed by 7500 Real- Time PCR System by assessing allelic discrimination based on TaqMan® methodology. Results. Patients (n = 13) who were treated with less than 2 mg of tacrolimus/day (0.024 ± 0.006 mg/kg/day) had the tacrolimus concentration-dose ratio larger than 150 ng/mL/mg/kg. In this group, 84.62% patients had CYP3А5 *3*3 allele. All of these patients had CYP3А4 *1*1/*1*1B allele. Regarding ABCB1 C3435T gene, 30.77% of patients had the TT gene variant, while 69.23% of our patients had CC and CT gene variants. Conclusion. Tacrolimus concentration-dose ratio greater than 150 ng/mL/mg/kg is cut-off value in patients subjected to renal transplantation which might point to patients who are poor CYP3A5 metabolizers and/or with dysfunctional P-glycoprotein.